Visualizing oral histories: A lab model using multimedia DH to incorporate ACRL framework standards into liberal arts education. Issue 2 (2nd October 2017) - White, Krista
ABSTRACT: Visualizing Oral Histories: Comics and Graphic Novels/Digital Humanities Lab, is a new model for digital humanities scholarship that other librarians can follow to create and teach similar DH labs attached to humanities courses at other institutions. The model includes a preliminary syllabus and preliminary assignment rubrics designed to integrate the Association of College and Research Libraries (ACRL) "Framework for Information Literacy for Higher Education" (ACRL Framework) into course assignments. Incorporation of a DH lab into a humanities course curriculum reimagines librarian roles and creates a pedagogical strategy that explicitly incorporates information literacy standards into the undergraduate course curriculum.